INFRARED SPECTROSCOPY OF NEARBY RADIO ACTIVE ELLIPTICAL GALAXIES - Mould, J; Reynolds, T; Readhead, T; Floyd, D; Jannuzi, B; Cotter, G; Ferrarese, L; Matthews, K; Atlee, D; Brown, M (2012)
In preparation for a study of their circumnuclear gas we have surveyed 60% of a complete sample of elliptical galaxies within 75 Mpc that are radio sources. Some 20% of our nuclear spectra have infrared emission lines, mostly Paschen lines, Brackett γ, and [Fe II]. We consider the influence of radio power and black hole mass in relation to the spectra. Access to the spectra is provided here as a community resource. © 2012. The American Astronomical Society. All rights reserved..